2005
DOI: 10.1002/jsfa.2138
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive evaluation of herbage from permanent meadows by near‐infrared reflectance spectroscopy: 1. Prediction of chemical composition and in vitro digestibility

Abstract: This study was implemented to evaluate the potential of near-infrared reflectance spectroscopy (NIRS) technology to estimate the chemical composition and in vitro digestibility of botanically complex herbage mixtures characterised, moreover, by a noteworthy variation among samples in the maturity of the forage plants. A total of 107 herbage samples harvested from permanent meadows located in the uplands of León (northwestern Spain) were analysed to determine their chemical composition. In addition, the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
(35 reference statements)
7
28
3
Order By: Relevance
“…The performance of our prediction models of NDF and ADF are comparable to previous studies on solid rumen content samples (Redjadj et al 2014), liquid rumen samples (Jean et al 2016) of herbivores, a wide range of feeds for ruminants (Belanche et al 2014) and meadow herbage (Andrés et al 2005). For the prediction of microbial-N (R 2 = 0.81; RMSEP = 1.25; RPD = 2.32) and lignin (R 2 = 0.84; RMSEP = 1.05; RPD = 2.57), the model performance was comparably lower than that of protein and NDF.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The performance of our prediction models of NDF and ADF are comparable to previous studies on solid rumen content samples (Redjadj et al 2014), liquid rumen samples (Jean et al 2016) of herbivores, a wide range of feeds for ruminants (Belanche et al 2014) and meadow herbage (Andrés et al 2005). For the prediction of microbial-N (R 2 = 0.81; RMSEP = 1.25; RPD = 2.32) and lignin (R 2 = 0.84; RMSEP = 1.05; RPD = 2.57), the model performance was comparably lower than that of protein and NDF.…”
Section: Discussionsupporting
confidence: 79%
“…For free-browsing ungulates, like moose, it is legitimate to expect heterogeneity in chemical fractions of lignin in the diet due to spatio-temporal variation in the type, availability and maturity of the feed. Anyway, the model parameters for the prediction of microbial-N and lignin concentrations in our study are comparable or even better than those observed for duodenal digesta (microbial-N: R 2 = 0.88, SEcv = 3.80; Atanassova et al 1998) and other herbage (Lignin: R 2 adj = 0.66, SEP = 7.18 g kg −1 DM; Andrés et al 2005).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations